Votes and violence : electoral competition and ethnic riots in India - Wilkinson, Steven, 1965- (Cambridge studies in comparative politics., 2004)
"Why does ethnic violence break out in some places and not others? More important, why do some governments try to prevent antiminority riots while others do nothing, or even actively encourage attacks? This book answers these questions through a detailed study of Hindu-Muslim riots in India, as well as case studies of Ireland, Malaysia, and Romania. It shows how electoral incentives at two levels interact to explain both where violence breaks out and, more importantly, why some states decide to prevent mass violence and others do not